Algae personification toxicity by GC–MASS and treatment by using material potassium permanganate in exposed basin - Ahmed Aidan Al-Hussieny; Esam Abd Alraheem; Haider Y. Lafta; Mohammed K. Shebli; Mohammed Jassim Obed Alfalahi; Allaa M. Aenab; S.K. Singh (Egyptian Journal of Petroleum)
This study was conducted to address algal toxins using potassium permanganate through the control of biomass growth of algae under following conditions value 25 ± 1 °C illumination intensity value 245 microeinstein/m2/s, using the culture media Chu-10 Modified for the purpose of development algae. We treated algal toxins belonging to groups of Neurotoxins, Hepatotoxins, Pyriproxyfen, Emodin, Brevetoxins-10 (A) and Cytotoxins using concentrations of potassium permanganate represented by 2, 4, 8 and 16 mg/l with alum concentration for each concentration of 30 mg/l, as the removal rate reached to 100% of the toxin blooms in concentrations of 8 and 16 mg/l respectively, through the examination of algal toxins mediated by GC–MASS compared to the standard, which diagnosed a range of algal toxins with C2H3C12NO formulas of synthetic C9H13NO2, C18H27NO3, C11H12N2O6, C11H17N3O, C10H17N3O, C9H15Br2NO, CH4N2O2, C11H17NO2, C13H9BrN2O3, C3H7NO4S, C20H29NO3, C15H10O5, C4H8O2 and C2H2Cl3NO the concentrations 2 and 4 mg/l turned toxic compounds into non-toxic compounds represented by C7H6O2, C5H6N2O, C12H11ClO4, C6H6O2, C12H10O4, C10H17N, C4H6O2 and C5H6N2O. The results showed reduced primary productivity of algae chlorophyll a result of substance to stop chloroplast for vital activity through the influence of the concentration of potassium permanganate values 0.571, 1.142, 0.583 and 1.713 mg/l respectively, compared to the standard of 114.2 mg/l. As diagnosed types of Algae producing toxins are represented by Microcystis aeruginosa, Microcystis flosaquae, Oscillatoria amoena, Oscillatoria amphibian, Oscillatoria boryana, Oscillatoria limnetica, Oscillatoria perornata, Phormidium ambiguum, Lyngbya digueti, Lyngbya major, Lyngbya nordgaadii, Lyngbya spirulinoides, Nostoc carneum, Nostoc spongiforme, Anabaena augstumalis, Chroococcus indicus and Chroococcus minor, as the dry weight of live Algae producing toxins is 17.342 g/l.